2020
DOI: 10.3390/vaccines8030426
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Vaccination for Children in Asian Countries: A Systematic Review of Economic Evaluation Studies

Abstract: Background: Evidence on costs and health benefits of pneumococcal conjugate vaccine (PCV) for children in Asian countries is limited but growing. As a region with a considerably high burden of pneumococcal disease, it is prominent to have a comprehensive overview on the cost-effectiveness of implementing and adopting a PCV vaccination program. Methods: We conducted a systematic review from Pubmed and Embase to identify economic evaluation studies of PCV for children in Asian countries up to May 2020. Data extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 63 publications
(382 reference statements)
3
7
0
Order By: Relevance
“…Obviously, this study also confirmed that PCV13 is more cost-effective than PCV10 with both prices. Our finding that pneumococcal vaccine would be cost-effective to be introduced in countries with high burden PD is linear with several previous studies that specifically focused in the Asia region [ 9 , 16 , 26 , 41 57 ]. Another finding, which confirmed that PCV13 is more cost-effective to be implemented than PCV10, is also in line with other studies that compared the use of PCV10 and PCV13 [ 16 , 26 , 49 , 53 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Obviously, this study also confirmed that PCV13 is more cost-effective than PCV10 with both prices. Our finding that pneumococcal vaccine would be cost-effective to be introduced in countries with high burden PD is linear with several previous studies that specifically focused in the Asia region [ 9 , 16 , 26 , 41 57 ]. Another finding, which confirmed that PCV13 is more cost-effective to be implemented than PCV10, is also in line with other studies that compared the use of PCV10 and PCV13 [ 16 , 26 , 49 , 53 ].…”
Section: Discussionsupporting
confidence: 88%
“…Several studies reported that vaccination was the most cost-effective intervention in reducing the incidence rate of PD [ 8 ]. In Asia, the children pneumococcal vaccination program was confirmed to be cost-effective and even cost saving in certain conditions [ 9 ]. The firstly developed pneumococcal conjugate vaccine (PCV), a 7-valent PCV (PCV7), has proven to reduce the incidence rate of PD significantly [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since vaccine hesitancy is already recognized by the World Health Organization as one of the 10 biggest threads to global health [ 112 ], identification of factors that enhance individuals’ intention to accept vaccination is crucial to increase vaccine uptake. Several systematic reviews suggest that vaccination against a variety of diseases (i.e., pneumococcal disease, varicella, tuberculosis) is a cost-effective or cost-saving intervention [ 113 , 114 , 115 , 116 ]. Additionally, a recent systematic review showed that the COVID-19 vaccination program appears to be a cost-effective or cost-saving intervention [ 117 ].…”
Section: Discussionmentioning
confidence: 99%
“…In children younger than 5 years of age, the number of PD cases in China ranks second in the world, accounting for 12% of the total cases worldwide [3]. Evidence shows significant vaccine effectiveness against PD [4][5][6][7][8][9],and economic evaluation studies show that vaccination is cost-effective [10][11][12][13]. Immunisation by pneumonia vaccine may reduce the increasing incidence of multidrug-resistance and cross-resistance due to the widespread use of antibiotics [14].…”
Section: Introductionmentioning
confidence: 99%